Metoda Sztywnych Elementów Skończonych w Zastosowaniu do Analizy Drgań Złożonych Układów Liniowych - Gawroński, W.; Kruszewski, J. (Engineering Transactions, 1972)
The method consists in replacing the actual system by a calculation system of stiff finite elements interconnected with linear characteristics. The application of the method to the calculation of undamped vibration forced by periodical forces has been discussed. An algorithm worked out on the basis of the stiff finite elements method has been programmed for a computer and applied in the Polish shipbuilding industry.